2021
DOI: 10.1371/journal.ppat.1009374
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 outbreak in a tri-national urban area is dominated by a B.1 lineage variant linked to a mass gathering event

Abstract: The first case of SARS-CoV-2 in Basel, Switzerland was detected on February 26th 2020. We present a phylogenetic study to explore viral introduction and evolution during the exponential early phase of the local COVID-19 outbreak from February 26th until March 23rd. We sequenced SARS-CoV-2 naso-oropharyngeal swabs from 746 positive tests that were performed at the University Hospital Basel during the study period. We successfully generated 468 high quality genomes from unique patients and called variants with o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…We did not find any mutation in the potential escape motifs, nor minority alleles in the samples that would hint at intra-host diversity. The variant distribution across RdRp is in line with the distribution observed in the global dataset, with the exception of a high frequency of a synonymous mutation in nucleotide position 15,324 (located in RdRp), recently described within a Basel-area specific lineage [30] (Supplementary Figure S5). We determined phylogenetic (pangolin nomenclature) lineages of the genomes carrying potential escape motif mutations [34], and found that they are distributed across 37 different lineages in 21 countries.…”
Section: Potential Escape Mutants In the Global Datasetsupporting
confidence: 85%
See 2 more Smart Citations
“…We did not find any mutation in the potential escape motifs, nor minority alleles in the samples that would hint at intra-host diversity. The variant distribution across RdRp is in line with the distribution observed in the global dataset, with the exception of a high frequency of a synonymous mutation in nucleotide position 15,324 (located in RdRp), recently described within a Basel-area specific lineage [30] (Supplementary Figure S5). We determined phylogenetic (pangolin nomenclature) lineages of the genomes carrying potential escape motif mutations [34], and found that they are distributed across 37 different lineages in 21 countries.…”
Section: Potential Escape Mutants In the Global Datasetsupporting
confidence: 85%
“…Degenerate base calls in the variant call other than N were not determining the exclusion of the genome from the dataset. Using our COVGAPgenomes pipeline [30], the sequences were first aligned to the Wuhan-1 reference [31] using mafft v7.467, point mutations were identified with snp-sites v2.5.1 [32]. The collected variants were then annotated using snpeff v4.5covid19 [33].…”
Section: Global Dataset Spatiotemporal Trends and Genome Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…See Refs. Nadeau et al (2021 ), Illumina COVIDSeq Test (2021 ), ARTIC (2021 ), Health Genome Center github (2021 ), Posada-Céspedes et al (2021) , Stange et al (2021 ), Chevin (2011 ), Seabold and Perktold (2010 ), Huisman et al (2020 ), Cori et al (2013 ) and Coronavirus (2021 ).…”
Section: Supplementary Datamentioning
confidence: 99%
“…MGEs cover different types of event and contexts such as public and private celebrations, festivals, religious events and pilgrimages, sporting and touristic events, and political meetings. The crucial role of MGEs in the global propagation of the disease has been evidenced in several countries, including China [ 3 ], Iran [ 4 ], Malaysia [ 5 ], Italy [ 6 ], Spain [ 7 ], France [ 8 ], Germany [ 9 ], Jordan [ 10 ], Malta [ 11 ], Switzerland [ 12 ], and Malawi [ 13 ]. Significant international efforts have been made to implement specific measures, risk assessment and surveillance, and event cancellations in order to prevent the spread of SARS-CoV-2 from MGEs [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%